Randomized Vitamin D Supplementation in Vitamin D Deficient Obese Children from West Virginia - Yoram Elitsur; Deborah L Preston (Archives of Clinical Gastroenterology - Peertechz Publications, 2016)
Objective: Vitamin D (Vit D) defi ciency is a very common problem in obese children, but clinical guidelines for maintenance or treatment have not been published for this population. The aim was to assess the benefi t of 2 months Vit D supplementation given to defi cient obese children from WV. Design: Vit D defi cient obese children were prospectively recruited. Exclusion criteria included <8 years, and medical conditions that may affect Vit D homeostasis. Participants were randomized into two  supplement groups: 5,000IU/day (Group A) or 50,000IU/week (Group B). Serum 25(OH)D levels were measured at baseline and post-treatment. Results: Sixty obese children were screened of whom 39 (65%) were defi cient (<20ng/ml). Of the 39  recruited, 26 completed the study. The mean serum 25(OH)D after 2 months treatment were signifi cantly higher in Group B (p= 0.02), but most reached normal levels (>30ng/ml).  Conclusions: Two months Vit D supplementation (5000IU/day or 50,000IU/week) was suffi cient to normalize 25(OH)D levels in Vit D defi cient obese West Virginian children.